Sports performance judgments: an update from a social cognitive perspective - Plessner, Henning; Ermark, Florian; Schütz, Lisa-Marie; Schweizer, Geoffrey (Asian journal of sport and exercise psychology, 2023)
In a seminal article (Plessner & Haar, 2006) a social cognition approach was proposed as framework to study how people judge their own or others’ performance in competitive sport contexts. An important goal of this work was to better understand the processes that underlie potential biases in judgments of sports performance and, thus, receive some hints on how to prevent them. Numerous studies have since been published in which judgments of sports performance have been subjected to scientific analysis. The present paper provides an updated overview on related research from the past 15 years. Again, it follows central building blocks of social information processing (i.e., information input, rules of information integration, situational influences, and characteristics/states of the judging person). Additionally, we organize this overview according to whether the research addresses judgments typically performed by athletes, officials, managers/coaches, or observers. On the one hand, it becomes clear that not all possible combinations of judging persons and information processes are addressed to the same extent in research, which opens up a number of future research tasks. On the other hand, it is suggested that future research in this area should not only be developed broadly, but also that the goal of further theoretical development should not be lost sight of.